Students' Mathematical Communication Skills in Mathematics Learning (International Journal of Innovative Research in Computer Science & Technology, 2023)
The capacity of students to communicate  mathematical ideas mathematically is one area in which it is  crucial to focus. The definition of mathematical  communication abilities, metrics for assessing mathematical  communication abilities, and learning models that are meant  to enhance students' mathematical communication abilities  are the main goals of this research. Systematic Literature  Review (SLR) is the methodology employed. Data was  gathered by recording and going over every publication  about mathematical communication abilities that contained  research that was comparable to this study. This study used  twenty publications that were found on DOAJ, Research  Gate, Science Direct, and Google Scholar. The research underscores the critical importance of diverse  factors in enhancing mathematical communication skills,  including collaborative learning, teacher feedback, cultural  awareness, digital tools, language proficiency, rubric-based  assessments, and more. Collaborative learning stands out as  notably effective, positively influencing students' capacity  to articulate and defend mathematical reasoning through  peer debates. Teachers' prompt and constructive feedback  contributes to the lucidity and accuracy of students'  mathematical explanations. Recognizing cultural diversity  fosters inclusivity and enhances the sharing of mathematical  concepts, while the use of digital tools enables alternative  means for expression and collaboration. The complex  relationship between language development and  mathematical communication abilities is emphasized,  highlighting the need for ongoing growth and a  comprehensive, inclusive strategy for the future of  mathematics education and communication.
Keywords: Mathematical; Communication; Skills